1996
DOI: 10.1007/s004030050083
|View full text |Cite
|
Sign up to set email alerts
|

Expression of SKALP/elafin during wound healing in human skin

Abstract: Skin-derived antileukoproteinase (SKALP), Key words SKALP • Wound healing • also known as elafin, is a proteinase inhibitor with Antileukoproteinase • Elastase specificity for polymorphonuclear leucocyte (PMN)-derived elastase and proteinase-3. SKALP is absent in normal human epidermis, but is strongly induced in Introduction inflammatory dermatoses such as psoriasis. SKALP is putatively involved in the regulation of cutaneous in-Proteinase activity is regulated systemically by numerous flammation by inhibitin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 2 publications
3
15
0
Order By: Relevance
“…For example, elafin seems to be important in the cellular differentiation of foetal to adult submandibular glands [124], and its degree of expression is related to the degree of differentiation in lung carcinomas [125,126]. Meanwhile, SLPI and elafin expression have been noted in response to cutaneous injury in humans [46,127], and SLPI has been shown to be an important endogenous factor in both cutaneous and oral mucosal wound healing [128][129][130]. Moreover, in the search for mechanisms delineating dermal scarring from oral scar-free healing, SLPI has been suggested as an active mediator.…”
Section: Alarm Antiproteases Promote Tissue Remodelling and Wound Heamentioning
confidence: 99%
“…For example, elafin seems to be important in the cellular differentiation of foetal to adult submandibular glands [124], and its degree of expression is related to the degree of differentiation in lung carcinomas [125,126]. Meanwhile, SLPI and elafin expression have been noted in response to cutaneous injury in humans [46,127], and SLPI has been shown to be an important endogenous factor in both cutaneous and oral mucosal wound healing [128][129][130]. Moreover, in the search for mechanisms delineating dermal scarring from oral scar-free healing, SLPI has been suggested as an active mediator.…”
Section: Alarm Antiproteases Promote Tissue Remodelling and Wound Heamentioning
confidence: 99%
“…[1][2][3] Skin injury has profound effects on keratinocyte differentiation, as shown by the induction of the hyperproliferation-associated cytokeratins 6 and 16. 4,5 Many other changes in gene expression patterns in the epidermis during wound healing have been described, including up-regulation of SKALP/elafin, 6 changes in integrin expression, 7-10 and alteration of cytokine profiles. 10,11 Changes in keratinocyte proliferation have been documented in a number of studies.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to normal skin where it is not detectable (Pfundt et al, 1996;Kamsteeg et al, 2010), elafin is abundantly secreted in diverse skin conditions exhibiting hyperproliferative features. These include psoriasis (Kamsteeg et al, 2010), wound healing (van Bergen et al, 1996), diverse skin neoplasms (Alkemade et al, 1993), and lichen planus (unpublished data from our lab). Our study not only revealed increased elafin expression in clGVHD, another disease characterized by keratinocytic hyperproliferation (Shulman et al, 2006), but also demonstrated a strong association between high elafin expression and epidermal thickening.…”
Section: Discussionmentioning
confidence: 84%